(untitled) (LACCEI, 2024)
Several investigations have demonstrated the compressive strength of mycelium grown on different types of substrates, however, there is room for further research on the compressive strength and absorption percentage of mycelium grown on different types of substrates due to the lack of mycelium growth on some substrates such as pine and mahogany sawdust grown in Honduras in past investigations. Because of this, it is important to investigate the properties of mycelium grown on organic substrates easily found in Honduras, such as pine sawdust, rice husks and hay. The research was carried out with the objective of determining the compressive strength and absorption percentage of mycelium cultivated on maicillo seeds, as well as to determine the growth of Pleurotus Ostreatus on pine sawdust and pine sawdust combined with rice husk and hay. The mycelium used were Pleurotus Ostreatus and Ganoderma Lucidum species. The manufacture of cylinders of Pleurotus Ostreatus mycelium cultivated on maicillo seeds cylinders of Pleurotus Ostreatus mycelium cultivated on pine sawdust and cylinders of Ganoderma Lucidum mycelium cultivated on maicillo seeds has been carried out. Additionally, pine sawdust and pine sawdust combined with rice husk and hay have been combined with Pleurotus Ostreatus mycelium to observe growth. The mycelium cylinders were subjected to compressive strength tests and the percentage of absorption was calculated, from which a comparative analysis was made between the different mycelium specimens, taking into account the results of the previous tests. For the cylinders of Pleurotus Ostreatus mycelium cultivated on maicillo seeds, a compressive strength of 0.03 MPa and an absorption percentage of 43.10% was obtained for the cylinders of Ganoderma lucidum, a maximum compressive strength of 1.91 MPa with a drying time of 3 months was obtained. Results which demonstrate that the longer the drying time of the mycelium, the higher the compressive strength is obtained.